Pengaruh Pupuk Kandang Diperkaya Batuan Fosfat Dan Pemangkasan Pucuk Terhadap Pertumbuhan Dan Produksi Okra (Abelmoschus esculentus L.) - Sa'diyah, Khalimatus -; Lukiwati, Dwi Retno; -, Sutarno - (JURNAL AGROPLASMA, 2022)
The research aimed to study the effect of manure enriched by rock phosphate and shoot pruning on the growth and yield of okra. The experiment used a 5 x 2 factorial based on randomized block design (RAK) with 3 replications, so that the obtained 30 units of treatment. The first factor was the type ofÂ  fertilization which consists of 5 levels, namely : P0 = TSP, P1 = poultry manure + TSP, P2 = cow manure + TSP, P3 = poultry manure + RP, P4 = cow manure + RP. The second factor was the shoot pruning which consists of 3 levels, namely : T0 = without shoot pruning and T1 = shoot pruning. Parameters measured number of branches, chlorophyll content,, flowering age, number of fruit, fruit weight, dry matter production and P uptake of stover on okra plants. Data were subjected to anova and followed by DMRT. The results showed that the type of fertilization and shoot pruning not significant the parameters of flowering age, chlorophyll content, dry matter production of stover and P uptake of stover on okra plants. The type of fertilization treatment and shoot pruning significant of the number of branches, number of fruit, and weight of okra fruit.